"Εμφύλιες" αψιμαχίες: Τα γλωσσικά όρια του πολιτισμικά διανοήσιμου υπό διαπραγμάτευση - Αντωνιάδης, Παναγιώτης (Aegean Working Papers in Ethnographic Linguistics, 2017)
In this article I draw on methodological tools from current sociolinguistics and discourse analysis in an attempt to map the dialectical relationship among language, gender and sexuality, based on data collected from conversations of a community of practice: a single-parent Greek family. In the first part, I try to locate the linguistic strategies through which participants emerge as gendered through their talk. Indexicality, language ideologies, and positive/negative politeness strategies figure prominently in the analysis. In the second part, I focus on the content of the same stretches of discourse vis-à-vis issues of sexuality. I suggest that the heteronormative status quo sets the very limits of what may be explicitly articulated, ultimately defining the realm of culturally intelligibility via nuanced concealments and explicit prohibitions, and show how speakers draw on a (largely predetermined and culturally saturated) pool of linguistic resources in order to construct and negotiate their gendered and sexual selves.